Translation of Processes in a Popular Book “Ask Barbara: The 100 Most-Asked Questions about Love, Sex and Relationships”: A Systemic Functional Linguistics (SFL) Approach to Translation Study - Jafar Sodiq; Sri Samiyati Tarjana; Mangatur Rudolf Nababan; Tri Wiratno (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2020)
AbstractThe SFL approach to translation studies should provide the technical terms as the linguistic evidence to account for the equivalence in the syntactical elements of the clause. This research aims at analyzing the translation of expository texts in a popular book. The research objectives are a) identifying the processes translated in the expository texts from English into Indonesian; b) identifying the techniques which tend to be used by the translator to translate the processes in the texts from English into Indonesian; and c) identifying the impacts in the translation quality of using the techniques to translate the processes in the popular book. The researcher employs a qualitative approach and a case study method. The data are taken from a document of a popular book of Ask Barbara: The 100 Most-Asked Questions about Love, Sex and Relationships, raters and experts and analyzed by the Spradley’s model of data analysis technique which includes domain analysis, taxonomy analysis, componential analysis, and the cultural theme or values. The results of this research reveal that from 315 clauses in the target language, there are 121 Material processes (40.7%), 102 Relational Attributive (34.3%), 57 Mental (19.2%), 18 Verbal (5.7%), 6 Existential (2%), 6 Behavioral (2%) and 5 Relational Identifying (1.7%) processes. The use of some techniques such as transposition, modulation, implicitation, explicitation, literal and deletion has contributed to the shifts of types of process in the translation and has resulted in the translation with high level of accuracy, acceptability, and readability.Keywords: Process Types, Expository Text, Translation Technique, Translation Quality AbstrakDalam pendekatan SFL untuk studi terjemahan, terdapat istilah teknis untuk mengukur kesepadanan dalam elemen sintaksis klausa. Penelitian ini bertujuan menganalisis terjemahan teks ekspositori dalam sebuah buku. Tujuan penelitian adalah a) mengidentifikasi proses menerjemahkan teks ekspositori dari bahasa Inggris ke bahasa Indonesia; b) mengidentifikasi teknik yang cenderung digunakan oleh penerjemah untuk menerjemahkan teks dari bahasa Inggris ke bahasa Indonesia; dan c) mengidentifikasi dampak dalam kualitas terjemahan dilihat dari teknik yang digunakan. Penelitian ini menggunakan pendekatan kualitatif dan metode studi kasus. Data diambil dari dokumen buku populer Ask Barbara: Ask Barbara: The 100 Most-Asked Questions about Love, Sex and Relationships, informan dan pakar dengan  model analisis data menurut Spradley yang mencakup analisis domain, analisis taksonomi, komponen analisis, dan tema atau nilai-nilai budaya. Hasil penelitian ini mengungkapkan bahwa dari 315 klausa dalam bahasa target, ada 121 proses Material (40,7%), 102 Atribut Relasional (34,3%), 57 Mental (19,2%), 18 Verbal (5,7%), 6 Eksistensial ( 2%), 6 proses Perilaku (2%) dan 5 Identifikasi Relasional (1,7%). Penggunaan beberapa teknik seperti transposisi, modulasi, implikasi, explikitasi, literal, dan penghapusan telah berkontribusi pada pergeseran jenis proses dalam terjemahan dan telah menghasilkan terjemahan dengan tingkat akurasi, penerimaan, dan keterbacaan yang tinggi.Kata kunci: Jenis Proses, Teks Ekspositori, Teknik Terjemahan, Kualitas Terjemahan